GOVERNMENT POLICY IMPLEMENTATION MEETING AND DOCTORS EQUALIZATION VALUES BASED ON JUSTICE (CASE STUDY IN DONGGALA REGENCY) - Edita Diana Tallupadang (Jurnal Pembaharuan Hukum, 2017)
AbstractThe purpose of this study is to know the construction of the implemen-tation of government policy in the fulfillment and distribution of current doctors; Obstacles to the implementation of government policies in the fulfillment and distribution of current medical staff; As well as the ideal reconstruction of local government policy in the fulfillment and equity of physicians based on the value of justice. The type of research used is the study of doctrinal law, the method of legal research conducted by examining the material legislation, library materials or secondary data. The approach of research conducted on the problems in this study using sociological juridical approach. The data in this research is analyzed by using qualitative method of descriptions. The results of this study are (1) Donggala District Government policy in meeting the needs of doctors in all districts of Donggala is by proposing through Central Sulawesi Provincial Health Office to obtain the quota of doctor of civil servant, PTT and doctor resident; (2) Constraints in the implementation of government policy in Fulfillment and even distribution of current medical staff are some doctors who have been placed pleading again to continue their education or move duties for following husband; and The ideal reconstruction of local government policy in the fulfillment and equity of physicians based on justice values is adjusted to the ratio and needs of the community, and plans to appoint physicians as non-permanent employees at the cost of local government. The Government of Donggala District can submit a Regent Regulation on the fulfillment and equity of doctors in Donggala District, as well as cooperation with private parties through private clinics and CSR improvement.